Karakteristik Densitas Dan Indeks Bias Minyak Atsiri Daun Jambu Kristal (Psidium Guajava) Menggunakan Metode Microwave Hydrodistillation Dengan Variabel Daya Dan Rasio Bahan : Pelarut - Erliyanti, Nove Kartika; Priyanto, Anugerah Dany; Pujiastuti, Caecilia (Jurnal Rekayasa Mesin, 2020)
Crystal seedless guava is a new horticultural commodity that is cultivated in Indonesia and has many benefits. Crystal seedless guava has the potential of essential oil to be extracted from the leaves. Extraction using the microwave hydrodistillation method is an alternative to improve the efficiency and effectiveness of the essential oil extraction process. The purpose of this study was to determine the effect of microwave power and the feed to solvent ratio toward the characteristics of density and refractive index of essential oil from crystal seedless guava leaves. The reduced size crystal seedless guava leaves were extracted by microwave using aquadest as solvents with the feed to leaves. The ratio of feed to solvents used in this study was 1:4, 1:5, 1:6, and 1:7 (weight/volume or w/v). The second variables were performed using various microwave powers of 300, 450, and 600 Watts. The extraction conditions were carried out at Â± 100 oC at one atmospheric pressure for three hours. The results showed that microwave powers and material to solvent ratios had significantly effect toward the density of essential oil from crystal seedless guava leaves. However, the variables had no significant difference in the value of the refractive index. The higher number of microwave powers and the solvent to feed ratios had a higher number of density. The highest density and refractive indexes were 0.948 grams/ml and 1,49862, respectively. The best extraction condition to extract the essential oil from crystal seedless guava leaves using microwave hydrodistillation was performed by microwave power of 600 Watt with 1:7 (w:v) as leaves to solvent ratio.